2010
DOI: 10.1111/j.1530-0277.2010.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Loading for Alcoholism and Offspring Behavior: Mediating and Moderating Influences

Abstract: Background Familial loading for alcoholism is an important marker of risk for early onset alcohol problems, but the early expression of this risk in community samples of children is understudied. Methods This study tested, for 452 eight- and ten-year old children, whether density of alcohol problems in their biological relatives was associated with externalizing behaviors that are risk factors for later alcohol problems. Results Density of alcohol problems in first- and second-degree biological relatives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 78 publications
1
37
1
1
Order By: Relevance
“…Being raised in a household headed by a single mother increased the risk of starting to drink by age 14, whereas having a father in the household decreased this risk (see also Dooley et al, 2005;Hayatbakhsh et al, 2008). Single parenthood may refl ect greater sociodemographic disadvantage (Molina et al, 2010) and was shown to relate to a number of other psychosocial risk factors (e.g., greater tolerance of deviance and friends' drinking and drug use). Identifi cation of the factors mediating this relationship would be important for the design of prevention programs targeted to children being raised by single mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being raised in a household headed by a single mother increased the risk of starting to drink by age 14, whereas having a father in the household decreased this risk (see also Dooley et al, 2005;Hayatbakhsh et al, 2008). Single parenthood may refl ect greater sociodemographic disadvantage (Molina et al, 2010) and was shown to relate to a number of other psychosocial risk factors (e.g., greater tolerance of deviance and friends' drinking and drug use). Identifi cation of the factors mediating this relationship would be important for the design of prevention programs targeted to children being raised by single mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived environment system encompasses variables refl ecting the child's perceptions of two major classes of social agents, parents and peers, and within each of these classes, variables with both proximal and distal relationships to child drinking. Measures of the family domain include the following: Mother-Child Relationship, a 6-item scale assessing intimacy and affection (Furman and Buhrmester, 1992; α = .76); Father-Child Relationship, a similar measure assessing the child's closeness to his or her father (α = .79); Confl ict with Parents, a 16-item measure (α = .88) assessing how often parents and children fi ght about chores, bedtimes, homework, friends, etc., a revision of the Issues Checklist used by Robin and Foster (1989); Parental Control, a 14-item scale (α = .69) assessing child versus parental say in decision-making regarding the above issues; Perceived Parent Approval of Child Drinking, a 4-item scale asking how their parents feel about a child their age drinking (α = .81); Parental Alcohol Socialization, a 5-item scale assessing the frequency of parent-child discussions about child drinking (α = .90; Donovan and Molina, 2008); Parental Approval of Child Drug Use, a 4-item scale assessing perceived parental approval for the use of cigarettes, marijuana, and other drugs (α = .92); Exposure to Mother Drinking and Exposure to Father Drinking, asking if the child had seen his or her mother or father drink alcohol in the past year; and Density of Family Alcohol Problems, a measure of the proportion of fi rst-and second-degree relatives with past or present alcohol problems as assessed by maternal reports on the Mann Family Tree (Mann et al, 1985;Molina et al, 2010).…”
Section: Measurement Of the Psychosocial Predictors Of Early Initiationmentioning
confidence: 99%
“…It has been suggested that CSAP show higher rates of behavioral problems at a younger age than their peers from community samples (Clark et al, 2004;Molina et al, 2010). These problems could contribute to the development of peer relationship difficulties at a later age, as described by van Lier and Koot (2010), who confirmed similar cascading effects in a community sample of school-aged children.…”
Section: Discussionmentioning
confidence: 83%
“…Maternal drug use during pregnancy can cause premature birth, slowed growth (Vucinovic et al, 2008) and low birthweight (Schuetze & Eiden, 2006;Behnke et al, 2013). In their childhood years, children of substance-abusing parents (CSAP) are at increased risk for developing anxiety problems (Diaz et al, 2008;Hill, Tessner, & McDermott, 2011), hyperactivity (Marmorstein, Iacono, & McGue, 2009;Sayal et al, 2009), aggressive behavior (Molina, Donovan, & Belendiuk, 2010), and reduced intellectual abilities (Bennett, Bendersky, & Lewis, 2008;Yang & Kramer, 2012). As adolescents, CSAP are more prone to develop mental disorders compared to their peers without substance-abusing parents (Diaz et al, 2008;Elkins, Fite, Moore, Lochman, & Wells, 2014;Hill et al, 2011;Kelley & Fals-Stewart, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation